2017
DOI: 10.1038/nutd.2016.48
|View full text |Cite
|
Sign up to set email alerts
|

Negative association between acrylamide exposure and body composition in adults: NHANES, 2003–2004

Abstract: Background/Objectives:Acrylamide is present in mainstream cigarette smoke and in some food prepared at high temperature. Animal studies have shown that acrylamide exposure reduces body weight. Prenatal exposure to acrylamide also has been linked to reduced birth weight in human. Whether acrylamide exposure is associated with altered body compositions in adults is not clear.Subjects/Methods:We selected 3623 subjects (aged ⩾20 years) from a National Health and Nutrition Examination Survey (NHANES) in 2003–2004 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…It is also used to manufacture adhesives and permanent press fabrics and in polyacrylamide gels for electrophoresis 3 . In 2002, ACR was discovered to be formed in food exposed to high temperature 4 from asparagine and carbonyl groups of glucose and fructose through the Maillard reaction 5 . Since then, many studies have addressed whether ACR carries a potential risk to human health 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also used to manufacture adhesives and permanent press fabrics and in polyacrylamide gels for electrophoresis 3 . In 2002, ACR was discovered to be formed in food exposed to high temperature 4 from asparagine and carbonyl groups of glucose and fructose through the Maillard reaction 5 . Since then, many studies have addressed whether ACR carries a potential risk to human health 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Other results suggested that exposure to acrylamide disrupt metabolic homeostasis and subsequently lead to obesityrelated disorders. As an electrophilic molecule, acrylamide is capable of reacting directly with sulfhydryl groups and amino residues of enzymes, receptors, and cytoskeletal proteins via its affinity for their nucleophilic sites; thus, acrylamide may affect a multitude of cellular processes, which has been proposed to formulate the basis of some of its toxic effects (15), and contribute to the causations observed in our current work. Secondly, gut microbial ecology also impacts on the metabolism and biotransformation of environmental toxins, and has been linked with the etiology of obesity.…”
Section: General Toxicitymentioning
confidence: 86%
“…Another possible biological mechanism between acrylamide exposure and growth is through oxidative stress and inflammation. Recently, acrylamide exposure was found to be inversely associated with several body composition measures in a sample of adults from the NHANES, and high oxidative stress was suggested as the mechanism involved (Chu et al 2017). During pregnancy, high acrylamide exposure can result in increased oxidative stress through increased expression of CYP2E1, resulting further in a heightened perinatal inflammatory status (Nguyen et al 2015;Wang et al 2003).…”
Section: Discussionmentioning
confidence: 99%